The Implementation and Integration of UIUX Design within the Joobify Application through the Utilization of the Lean UX Methodology - Nanuru, Freedom George; Tuhuteru, Hennie; Nivaan, Goldy Valendria (PT Mattawang Mediatama Solution, 2023)
The development of digital technology has brought fundamental changes to various aspects of human life, including job searching. The utilization of digital technology in job search has provided broader and more flexible access for job seekers. The purpose of this writing is to build a user experience (UX) and personalization system to ensure that received information is conveyed clearly without being overwhelming. The method used is Lean User Experience (UX), which focuses on reducing time and costs in the development process. Data collection techniques include literature studies and questionnaires. The results obtained indicate the successful implementation of the interface on the Joobify website, with a success rate exceeding 80% in usability test using the “Maze” website platform. In conclusion, integrating and designing UI/UX on the Joobify website can help job seekers quickly access job vacancy information, save transportation costs, and expand their job search reach based on their skills and interests